Adverse associations between maternal deoxynivalenol exposure and birth outcomes: a prospective cohort study in China - Tianqi Tan; Tingting Chen; Wenwen Zhu; Lin Gong; Yizhong Yan; Qian Li; Li Chen; Yiling Li; Jialin Liu; Yanan Li; Xuefeng Yang; Liping Hao; et al. (BMC Medicine, 2023)
Abstract Background Deoxynivalenol (DON), one of the most prevalent mycotoxins, has been found to cause fetal growth retardation in animals. However, limited evidence exists regarding its effects on pregnant women. Methods Maternal urinary concentration of total DON (tDON) and free DON (fDON) in the second trimester was measured using liquid chromatography with tandem mass spectrometry. Provisional daily intake (PDI) of DON was calculated based on tDON concentration. Linear and logistic regression models were used to evaluate the association between DON exposure levels and birth weight, birth length, and the risk of small for gestational age (SGA). Results Among 1538 subjects, the median concentrations of tDON and fDON were 12.1 ng/mL and 5.1 ng/mL, respectively. The PDI values revealed that the median DON intake was 0.7 µg/kg bw, and 35.9% of the total population exceeded the provisional maximum tolerable daily intake (PMTDI) of 1 µg/kg bw. Compared with the lowest tertile, birth weight decreased by 81.11 g (95% CI: -127.00, -35.23) for tDON (P-trend < 0.001) and 63.02 g (95% CI: -108.72, -17.32) for fDON (P-trend = 0.004) in the highest tertile. Each unit increase in Ln-tDON and Ln-fDON was also inversely associated with birth weight. Furthermore, compared to those who did not exceed PMTDI, pregnant women whose PDI exceeded PMTDI had lower birth weight (β = -79.79 g; 95% CI: -119.09, -40.49) and birth length (β = -0.21 cm; 95% CI: -0.34, -0.07), and a higher risk of SGA (OR = 1.48; 95% CI: 1.02, 2.15) in their offspring. Similar associations with birth weight, birth length, and SGA were found when comparing the highest tertile of PDI to the lowest tertile (all P-trend < 0.05). Conclusions Maternal DON exposure is related to decreased birth weight. Our findings implicate that DON exposure during pregnancy may cause fetal growth faltering, and measures should be taken to reduce DON exposure in pregnant women.